1991
DOI: 10.1073/pnas.88.8.3060
|View full text |Cite
|
Sign up to set email alerts
|

An idiotypic network model of AIDS immunopathogenesis.

Abstract: Considerations from a network theory of the immune system suggest that human immunodeficiency virus and allogeneic stimuli may act synergistically to cause AIDS. The immune responses to these stimuli include two components that are directed against each other. In some AIDS risk groups other antigens that mimic major histocompatibility complex antigens may substitute for allogeneic stimuli. Implications for the prevention of AIDS are discussed.The idea that human immunodeficiency virus (HIV) is the sole cause o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…Anti-idiotype phenomena as a cause of immune system destabitization in the pathogenesis of AIDS were first suggested by Ziegler & Stitcs [26]. Hoffmann and co-workers [5] presented a network model of AIDS pathogenesis which includes idiotypicinduced autoantibodies. These, possibly, react with the MHC class II image of T cell receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-idiotype phenomena as a cause of immune system destabitization in the pathogenesis of AIDS were first suggested by Ziegler & Stitcs [26]. Hoffmann and co-workers [5] presented a network model of AIDS pathogenesis which includes idiotypicinduced autoantibodies. These, possibly, react with the MHC class II image of T cell receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-lymphocyte antibodies are able to induce helper cell defects in vitro [16], and an association of helper cell defects to anti-CD4 cell antibodies in vivo has been demonstrated [34]. The network model presented by Hoffmann et al [5] especially focuses on autoimmune reactivity against regulatory suppressor (CD8 *) T cells. Therefore, the induction of defects in helper and suppressor cells could be a major mechanism of anti-lymphocyte antibody activity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Habeshaw et al have advanced the hypothesis that gp120 mimics a portion of an MHC-like protein, and thus can further potentiate an autoimmune GVHD-like reaction [43]. A variation of this hypothesis has been advanced by Hoffmann and colleagues [44,45], who have used the observation that patients with HIV infection have high levels of anti-collagen antibodies as evidence for a GVHD reaction [46].…”
Section: Anti-histone Antibodies In Hiv Infectionmentioning
confidence: 99%
“…Indeed, the gp120 component of the HIV Env has the potential to mimic major histocompatibility complex class II. 66 As such, it is foreseeable that the idiotypic cascade induced after the initiation of the anti-HIV humoral immune response includes anti-HIV Abs that mimic CD4, as well as anti-anti-HIV Abs that mimic MHC II and bind CD4 mimicking anti-HIV Abs or CD4 itself. Several investigators have independently demonstrated the presence of anti-CD4 Abs in HIV-infected individuals, and some reports have linked these Abs with progression toward AIDS.…”
Section: Utilizing Idiotypic Repertoire Freeze To Maintain Vaccine Inmentioning
confidence: 99%